Implementasi Project-Based Learning untuk Meningkatkan Keterlibatan dan Pemahaman Awal Siswa tentang Perubahan Iklim di Kelas IV SD: Penelitian - Juliana M. Sumilat; Kurniaty; Abigail M. Rotikan; Joyhelga C. Maramis; Avril P. Manikome; Tiara I. Kaligis; Rafael Wuisan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the application of the Project-Based Learning (PjBL) model on climate change material in grade IV of St. Yohanes Tomohon Catholic Elementary School. The method used was Classroom Action Research (CAR) conducted in one meeting involving 40 students. The lesson began with an apersepsi using pictures of environmental change, followed by an experiment entitled “Ice Melts Faster” and a project activity in the form of poster making. The results showed that 80% of students were active in the apersepsi and 90% were involved in the experiment. The project products showed that 78% were in the good category, while learning completeness reached 75%. These results indicate that the application of PjBL can increase student engagement and initial understanding, although in-depth understanding has not been achieved due to time constraints. Thus, models are effective as initial strategies for ac.